(3GdQSGFd GdeQSdI hGdhSGFd GdehUdIs - (3fhQ GdOjf CHh GdMSf Ydj Hf GdMSf Hf YHO Gddg Hf MSjf Hf YeQ Hf YHO GdQMef GdYWGS Ydhj GdMSjfj,J (B1172 (3g` s
(3ChdgG (B:s
" (3hYO Gddg GdP (B[(3jf (B] (3GdeNQL eeG jcQghf , hGdQRb ef MjK dGjMJSHhf s
(3BNQgG (B:s
(3hCYWGg GdcQGeI HGdSdGeI Zdi OGQ GdebGeI Hjf BHGFg hENhGfg hCYeGeg efce (B" s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQi s
(3eRjfI HGdMeQI ai HYV GdehGVY hHBNQgG agQSJs
(3HgG HYV GdENJdGa Yf GdfSNI GdSGHbI s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs